Memory deficit following resection of an intraventricular myxoid glioneuronal tumor impinging on the bilateral fornix: A case report - Stasenko, Alena; Kaestner, Erik; Rodriguez, Jonathan; Kohli, Jiwandeep S.; Farid, Nikdokht; Goodwill, Vanessa; Schwartz, Marc S.; Schulte, Jessica D.; McDonald, Carrie R. (Frontiers in Oncology, 2023)
Recently recognized as a distinct entity, a myxoid glioneuronal tumor (MGNT) is a rare, low-grade central nervous system tumor. MGNTs are commonly located at the septum pellucidum or in the third ventricle, increasing the likelihood of tumor or treatmentrelated damage to adjacent structures critical for memory, such as the fornix. Though there have been a handful of case reports of neurosurgical and oncological outcomes of MGNTs, memory outcomes following resection of MGNTs adjacent to the fornix have not been previously reported. We present a case of a high functioning female for whom an MRI revealed an incidental finding of an intraventricular tumor adjacent to the fornix bilaterally. The patient underwent resection of the tumor followed by MRI surveillance without additional oncologic intervention. Due to reported cognitive problems, the patient was referred for serial neuropsychological evaluations. Post-operative MRI following resection revealed cytotoxic edema followed by selective, progressive atrophy of the bilateral anterior fornices. Post-surgically, the patient developed an isolated verbal memory impairment, which persisted one-year post resection with minimal improvement. The memory impairment impacted the patient's everyday functioning, including the ability to work in a cognitively demanding job. This unique case demonstrates the critical role of the bilateral fornix in verbal memory and underscores the importance of a careful risk/benefit analysis when considering neurosurgical intervention to MGNTs and other intracranial lesions adjacent to this structure during neurosurgical planning.